Production and characterization of FE-C-AL cast iron - Shaha, Sugrib Kumar (Kulliyyah of Engineering, International Islamic University Malaysia, 2010)
Cast iron is the most useful industrial ferrous alloy, which mainly contains conventional Fe-C-Si alloy system. Its room temperature properties are good but with increment of temperature, the properties decline. However, the Fe-C-Al alloy system can prevent this behaviour. It improves the room temperature properties as well as high temperature properties. In this work, the thermal behaviour of cold set resin bonded sand mould was simulated by computer simulation software. In order to verify the model, the microstructure and properties of Fe-C-Al system and the conventional Fe-C-Si system were investigated and compared with each other. It showed that the predicted and experimental values were nearly the same. For the experimental verification, two batches of cast irons were cast. In first batch, the pig iron (Sorel metal), mild steel and Al and in the second batch, high silicon pig iron and mild steel were melted in an induction furnace at 13500C and poured in the sand mould at 13000C. The structures were characterized using SEM, FESEM, EDX and XRD. After casting two stages heat treatment operation was performed. After that, hardness, fracture toughness, wear, corrosion, and oxidation resistance were measured in as cast condition while as hardness was measured for heat treated sample following ASTM and ASM metal hand book. Experimental results show that Fe-C-Al alloy system cast iron has better properties than conventional one. Fe-C-Si and Fe-C-Al alloys have different microstructure in terms of graphite distribution and matrix structure. It also shows that Fe-C-Al alloy has reduced the chilling tendency of the cast iron. For Fe-CSi alloy hardness varies from 78.78 to 95.1 HRB whereas for other variety, it ranges from 103.1 to 110.2 HRB for 10 mm to 2 mm thickness. The absorption of impact energy for both alloys is nearly the same at room temperature, but at high temperature (2000C) Fe-C-Si alloy shows lower energy absorption. Wear rate of the Fe-C-Al alloy is 3.320×10-5 to 8.155×10-5mm3/N/m whereas Fe-C-Si alloys wear rate is 12.42× 10-5 to 98.87667 × 10-5 for 25 to 3000C temperature. The oxidation and corrosion resistance of Fe-C-Al is about 3 to 5 times higher than the conventional cast iron.